Critical Infrastructures: Risk and Vulnerability Assessment in Transportation of Dangerous Goods Transportation by Road and Rail - Vamanu, Bogdan I.; Gheorghe, Adrian V.; Katina, Polinpapilinho F. (Topics in Safety, Risk, Reliability and Quality,, 2016)
This book addresses a key issue in today's society: the safer transport of dangerous goods, taking into account people, the environment and economics. In particular, it offers a potential approach to identifying the issues, developing the models, providing the methods and recommending the tools to address the risks and vulnerabilities involved. We believe this can only be achieved by assessing those risks in a comprehensive, quantifiable and integrated manner. Examining both rail and road transportation, the book is divided into three sections, covering: the mature and accepted (by both academia and practitioners) methodology of risk assessment; the vulnerability assessment - a novel approach proposed as a vital complement to risk; guidance and support to build the tools that make methods and equations to yield: the Decision Support Systems. Throughout the book, the authors do not endeavor to provide THE solution. Instead, the book offers insightful food for thought for students, researchers, practitioners and policymakers alike.